In vitro performance of implant-supported monolithic zirconia crowns: Influence of patient-specific tooth-coloured abutments with titanium adhesive bases. Issue 7 (July 2015) - Rosentritt, Martin; Rembs, Andreas; Behr, Michael; Hahnel, Sebastian; Preis, Verena
Abstract Objective To investigate the influence of the combination of patient-specific abutments and titanium adhesive bases on the long-term in vitro performance of anterior crowns. Methods Ten systems of screw-retained implant and adhesive base combinations (n = 8/group) were restored with zirconia or polyetherketone (PEEK) abutments and identical full-anatomical zirconia crowns. For simulating clinical anterior loading, implants were fixed at an angle of 135° and submitted to prolonged thermal cycling and mechanical loading (TC: 6 × 3000 cycles, 5 °C/55 °C; ML: 100 N, 3.6 × 106 cycles) to cause and register fatigue failure. Failed restorations were examined by means of scanning electron microscopy. Surviving restorations were loaded to fracture. Data (mean ± standard deviation) were statistically analyzed (ANOVA; Bonferroni; Kaplan–Meier-Log-Rank; α = 0.05). Results Seven systems survived TCML without any failure. The other three systems showed loosening and fracturing of the screw (0.4–1.6 × 106 loadings) or debonding between base and abutment (0.002–3.4 × 106 loadings). None of the systems showed any fracture of the crown or failed bonding between abutment and crown. The Log-Rank test showed significant (p = 0.000) differences. Fracture data significantly varied (ANOVA p = 0.000) between the individual systems (minimum: 371 N; maximum: 763 N). Failures were mostly caused by bending or fracturing of the screw and in three cases by fracture of the abutment. Conclusions Anterior implant-supported zirconia crowns on titanium adhesive bases and bonded patient-specific zirconia abutments provided good in vitro performance and high fracture resistance. Sufficient high torque moments and early re-screwing may be advised. Clinical relevance Most adhesive base and abutment combinations may be appropriate for anterior application. Individual improvements may contribute to enduring success.